Three new species of Exampithoe from Australia and New Zealand (Ampithoidae: Amphipoda: Crustacea) - Hughes, Lauren E.; Peart, Rachael A. (Zootaxa, 2015)
Three new species of Exampithoe are described from Australia and New Zealand. Material described here corroborates the peculiar mandibular palp variability, with either a two- or three- articulate palp reported for species within the genus Exampithoe compared to the absence of the mandibular palp in Melanesius. The Exampthoinae remain a Southern Hemisphere subfamily with nine described species.